Using the ‘Expert Performance Approach’ as a Framework for Examining and Enhancing Skill Learning: Improving Understanding of How Experts Learn - Williams, Andrew Mark; Fawver, Bradley; Hodges, Nicola J. (Frontline Learning Research, 2017)
The expert performance approach is reviewed as a systematic framework for the study of expertise. Its potential as a framework for the study of how experts learn is presented. The need to develop representative tasks to capture learning is discussed, as is the need to employ process-tracing measures during acquisition to examine what actually changes during learning and to use realistic retention and transfer tests. A focus on individual differences in learning within groups of expert performers is recommended in order to identify characteristics of more efficient and effective learning. The identification and study of how experts learn will enhance our understanding of skill acquisition and how this may be promoted using instructional interventions and practice opportunities. The challenge for scientists is to generate knowledge that helps those involved in facilitating skill acquisition continue to help experts acquire and refine skills across professional domains.